Bone repair assessment of critical size defects in rats treated with mineralized bovine bone (Bio-Oss®) and photobiomodulation therapy: a histomorphometric and immunohistochemical study - Torquato, Letícia Cavassini [UNESP]; Suárez, Eduardo Antonio Chelin [UNESP]; Bernardo, Daniella Viscensotto [UNESP]; Pinto, Isis Luzcybel Ribeiro [UNESP]; Mantovani, Ludmilla Oliveira [UNESP]; Silva, Thiago Igor Lemes [UNESP]; Jardini, Maria Aparecida Neves [UNESP]; Santamaria, Mauro Pedrine [UNESP]; De Marco, Andrea Carvalho [UNESP] (Springer Nature, 2021)
This study aimed to investigate the effects of administering photobiomodulation therapy (PBM) with bovine bone matrix on critical size defects in rats. Seventy-two adult male rats (albinus, Wistar), 90 days old, were used. Defect of 5 mm in diameter was made in their calvaria. The animals were divided into 4 groups: C-blood clot, B-Bio-Oss®, L-PBM, B+L-Bio-Oss®+PBM. Each group has been subdivided into 07, 30, and 60 days of observation. For PBM, a low GaAlAs energy of 660 nm was irradiated, total energy density of 45 J/cm2. PBM was conducted in a trans-surgical form once only. For immunohistochemistry, a semi-quantitative analysis was made of expression of osteoprotegerin (OPG), nuclear kappa B-factor ligand receptor activator (RANKL), and tartrate-resistant acid phosphatase (TRAP). All histomorphometric data were statistically analyzed by ANOVA and Tukey test, significance level of 5%. The groups that showed the highest proportion of neoformation were L (0.39% ± 0.13) and C (0.37% ± 0.97), but groups B and B+L had larger defect size (C-1.75 mm2 ± 0.40, B-3.02 mm2 ± 0.63, L-2.45 mm2 ± 0.53, B+L-3.23 mm2 ± 1.01). In immunohistochemistry, groups B and B+L had higher immunostaining scores for OPG and RANKL at 60 days, and TRAP immunostaining increased in all groups at 30 days, but group L was the only one to present specimens with score 0. Although, at 60 days, groups L and C presented the highest proportion of bone neoformation, at 30 days group B+L had more than twice as much bone neoformation as group B, the choice of treatment application should depend on the aim of the treatment.
Keywords: Biocompatible materials; Bone regeneration; Bone transplantation; Immunohistochemistry; Low-level light therapy